Mar do sul da China: atuação da política externa chinesa nas disputas das ilhas - (:unkn) unknown (Universidade Federal do Pampa, 2018)
The South China Sea is one of the most important scenarios lately, and its archipelagoes are among the nations of Southeast Asia and East Asia. Beyond China, the countries that claim the most are Vietnam and the Philippines, triggering a regional tension around litigation involving regional and extra-regional powers. The following research problem arises: does China seek territorial expansion through the islands? The hypothesis we want to uncover is that China's interest in the islands is to maintain its socioeconomic development. Therefore, the main objective of this research is to explore the main elements of Chinese foreign policy, to understand the Chinese performance in the archipelagos during the years 2002 to 2017, and to analyze treaties and the role of the ASEAN (Association of Southeast Asian Nations) in the disputes of the islands. For that, we used books, periodicals, articles, and news conducting a case study, through a historical analysis. Through this research it was possible to verify that the main objective of the Chinese foreign policy is to maintain the socio-economic advance of the country, and for this Beijing needs to have a stable environment with its neighbors. However, the South China Sea issue is far from having a solution, as there has been no major progress in the negotiations since 2002.
South China Sea: China's foreign policy on island disputes
Keywords: Mar do Sul da China; Política externa chinesa; Vietnã; Filipinas; South China Sea; Chinese foreign policy; Vietnam; Philippines; CNPQ::CIENCIAS SOCIAIS APLICADAS